Tolerogenic dendritic cells show gene expression profiles that are different from those of immunogenic dendritic cells in DBA/1 mice. (17th February 2016) - Lee, Eun Gae; Jung, Nam-Chul; Lee, Jun-Ho; Song, Jie-Young; Ryu, Sang-Young; Seo, Han Geuk; Han, Sung Gu; Ahn, Keun Jae; Hong, Kwan Soo; Choi, Jinjung; Lim, Dae-Seog
Abstract: Tolerogenic dendritic cells (tDCs) play an important role in inducing peripheral tolerance; however, few tDC-specific markers have been identified. The aims of this study were to examine whether tDCs show a different gene expression profile from that of immunogenic DCs and identify specific gene markers of each cell type, in DBA/1 mice. tDCs were generated by treating immature DCs (imDCs) with TNF-α and type II collagen. The gene expression profiles of mature (m)DCs and tDCs were then investigated by microarray analysis and candidate markers were validated by quantitative real-time reverse transcription-polymerase chain reaction (qRT-PCR). Supervised selection identified 75 gene signatures, 63 of which were consistently upregulated in mDCs and 12 of which were upregulated only in tDCs. Additionally, 10 genes were overexpressed or equally expressed in both tDCs and mDCs. Scin (tDC-specific genes) and Orm1, Pdlim4 and Enpp2 (mDC-specific genes) were validated by real-time qRT-PCR. Taken together, these results clearly show that tDCs and mDCs can be identified according to their expression of specific gene markers.